Loan loss provisioning practices in Indian Banking System - Gupta, Neena (2014)
This paper has examined the India’s banking system, looking specifically at the structure, legislation and regulatory bodies that govern and dictate how the banking system is defined which is continuously exposed to Asian financial crises, Global Financial crises and Eurozone crises. This paper analyses the X- Efficiencies and further the loan loss provisioning practices during the period 2006-2012. The main finding include that Indian banks were affected by the crises and X-Efficiencies are not the significant part when it comes to loan loss provisioning. The study finds a significant relationship between net income and Loan Loss Provisions but finds no evidence of pro/countercyclical and capital management.